Detection value of free cancer cells in peritoneal washing in gastric cancer: a systematic review and meta-analysis (Clinics, 2016)
Intraperitoneal free cancer cells in gastric adenocarcinoma are associated with a poor outcome. However, the true prognostic value of intraperitoneal free cancer cells is still unclear, leading to a lack of consensus in the management of gastric cancer. The aim of the present study is to perform a systematic review and meta-analysis to analyze intraperitoneal free cancer cells-positive patients with regard to tumor oncologic stage, recurrence, grade of cellular differentiation, and survival rates and to analyze the clinical significance of intraperitoneal free cancer cells with regard to prognosis. Databases were searched up to January 2016 for prognostic factors associated with intraperitoneal free cancer cells, including oncologic stage, depth of neoplasm invasion, lymph nodal spread, differentiation grade of the tumor, and recurrence and survival rates. A total of 100 studies were identified. Meta-analysis revealed a clear association between intraperitoneal free cancer cells and a poor prognosis. intraperitoneal free cancer cells -positive patients had higher rates of nodal spread (risk difference: 0.29; p